"No Alcohol Is Recommended, But . . .": Health Care Students' Attitudes About Alcohol Consumption During Pregnancy. (11th May 2017) - Coons, Kelly D.; Watson, Shelley L.; Yantzi, Nicole M.; Lightfoot, Nancy E.; Larocque, Sylvie
Canadian findings suggest that health care providers require further training and education to support their work preventing fetal alcohol spectrum disorder (FASD). However, the knowledge and training of health care students in relation to FASD remains largely unexplored. The purpose of this study was to understand the attitudes and beliefs of health care students about alcohol use during pregnancy. Twenty-one health care students participated in a scenario-based vignette about alcohol consumption during pregnancy. Although almost all students recognized that no alcohol consumption during pregnancy is the safest recommendation, many students recounted that this advice is not always conveyed during encounters with their pregnant patients. Three primary themes related to students' attitudes concerning alcohol use during pregnancy were identified. Health care professionals in training need further education about the risks of alcohol consumption during pregnancy and the potential health outcomes associated with prenatal alcohol exposure.